Pyrogenic Influence n Geochemistry Migration Ability of Heavy Metal - Buts, Yu. V.; Krainyuk, O. V.; Barbashin, V. V.; Kobzin, V. G. (Man and Environment. Issues of Neoecology, 2018)
Purpose. Investigation of dynamics of geochemical migration ability of heavy metals as a result of the effect of man-made loading of pyrogenic origin. Methods. Analytical: atomic absorption analysis, pH-metric; the range of precipitation of hydroxides and the region of predominance of soluble hydroxocomplexes have been studied by constructing concentration-logarithmic diagrams (CRLs). Results. The results indicate the transformation of their migration properties. The diversity and versatility of behavior of chemical elements in environmental components after the fire was noted. In different ecological conditions, it is possible to observe a wide range of quantitative values of geochemical migration or accumulation of any particular chemical element.Analytical results show that the contents of migrant elements, pH values, areas of incidents, which are approximately in the same conditions, but passed by the grass or upper fire differ quite tangibly.Heavy metals that hit the environment can form difficult soluble hydroxides. In addition, in the soil solution, there is a probability of the formation of hydroxocomplexes with different amounts of hydroxide ions by metals. The range of precipitation of hydroxides and the region of predominance of soluble hydroxocomplexes have been studied by constructing concentration-logarithmic diagrams.On the basis of the calculations it can be argued that the influence of the technogenic loading of pyrogenic origin on the geochemical migration of heavy metals takes place. Compounds Fe3+ at the pH = 4.5-14, Cu2+ at pH = 7-14, Cr2+ at pH = 7-9, Zn2+ at pH= 8-11, Ni2+  at pH = 8-14 have the lowest migration potential. Compounds Pb2+ at pH = 9-12, Fe2+ - pH = 9.5-14 have the lowest migration potential also. In a more acidic_____________________________________________________© Буц Ю. В., Крайнюк О. В.,  Барбашин В. В., Кобзін В. Г. , 2018environment, soluble substances are formed, but at a pH increase of only 0,5-1, they can decrease their mobility by an order of magnitude, which contributes to their concentration in the soils after the fire.In a neutral soil reaction, most of the heavy metals (Al, Cr, Zn, Cu, Fe (II), Ni) are in a slightly soluble form (in the form of hydroxides), with their migration capacity insignificant, which leads to the accumulation of these chemical elements in the soil .In a separate group it is necessary to allocate heavy metals moving in a neutral environment (Fe (II), Cd, Co, Mg, Mn). Any increase in pH values contributes to their fixation. Conclusions. The obtained calculations can be used to predict the geochemical migration of heavy metals in soils after the man-made consequences of emergencies of pyrogenic origin.